Optimized Protocol for Regeneration of the Conjunctival Epithelium Using the Cell Suspension Technique. Issue 4 (April 2019) - Bertolin, Marina; Breda, Claudia; Ferrari, Stefano; Van Acker, Sara Ilse; Zakaria, Nadia; Di Iorio, Enzo; Migliorati, Angelo; Ponzin, Diego; Ferrari, Barbara; Lužnik, Zala; Barbaro, Vanessa
Abstract : Purpose: To develop autologous tissue-engineered conjunctival epithelial sheets to be used as advanced therapy medicinal products for severe ocular surface disorders involving the conjunctiva. Methods: Methods used aimed at 1) mapping the conjunctiva for identification of the stem cell location, 2) establishing proper cell culturing conditions, 3) identifying the proper scaffold, and 4) characterizing the conjunctival grafts better. For these purposes, immunostaining and PAS staining, serial cultivation of cells, and quantitative polymerase chain reaction ([INCREMENT]Np63α and MUC5AC) were performed. Results: The inferior fornix represents the ideal area where to take the conjunctival biopsies from, with at least +3.58% of clonogenic colonies and higher percentages of stem cells compared with other areas, as confirmed by [INCREMENT]Np63α expression levels (6.79% ± 1.18%). The standard culture conditions are necessary when cells are cultured on bare plastic, while animal-free media can be used for conjunctival cell culture on the scaffold. Fibrin glue represents the ideal scaffold for production of epithelial conjunctival grafts because it allows physiological expression of the main conjunctival cell markers, with K19 as the ideal one (98.5% ± 0.5% positive cells). The presence of goblet cells (6.3% ± 1.3%) and expression of the stem cell marker [INCREMENT]Np63α (1.65% ± 0.35% positive cells) were also assessed. Conclusions: Our findings pave the way for ex vivo cultivation of conjunctival epithelial cells onto a scaffold using the cell suspension technique by means of animal-free media. This would allow us to obtain conjunctival grafts for clinical purposes, thus giving a therapeutic option to patients with conjunctival diseases refractory to current therapies. Abstract : Supplemental Digital Content is Available in the Text.